1976
DOI: 10.1128/aac.9.4.595
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Efficacy of Sch 20569 and Amikacin Against Gentamicin-Sensitive and -Resistant Organisms

Abstract: Sch 20569 is a semisynthetic derivative of gentamicin with activity against many gentamicin-resistant gram-negative bacilli. We compared its bactericidal action with that of gentamicin and amikacin against 171 clinical isolates of Enterobacteriaceae, Staphylococcus aureus, and Pseudomonas aeruginosa. Sch 20569 and amikacin showed markedly greater activity than gentamicin against Escherichia coli, Klebsiella, Enterobacter, Citrobacter, and indole-positive Proteus, primarily by virtue of their lethal effect on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
6
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 3 publications
4
55
6
1
Order By: Relevance
“…Its antimicrobial spectrum is similar to that of gentamicin with an added advantage that an increasing number of Enterobacteriaceae possess adenylating enzymes mediating resistance to gentamicin, but not to netilmicin (4,10,16,21,28). Animal studies indicate that substantially less ototoxicity and nephrotoxicity result from repeated doses of netilmicin than of gentamicin (9,12,16).…”
mentioning
confidence: 88%
“…Its antimicrobial spectrum is similar to that of gentamicin with an added advantage that an increasing number of Enterobacteriaceae possess adenylating enzymes mediating resistance to gentamicin, but not to netilmicin (4,10,16,21,28). Animal studies indicate that substantially less ototoxicity and nephrotoxicity result from repeated doses of netilmicin than of gentamicin (9,12,16).…”
mentioning
confidence: 88%
“…Netilmicin (Sch 20569), an agent differing from sisomicin by the presence of an ethyl group at the 1-N position of the deoxystreptamine moiety, has recently been provided for in vitro work. Initial animal toxicity studies indicated that this agent may be less oto-and nephrotoxic than gentamicin (5). Our study compares the in vitro activity of netilmicin with those of gentamicin, tobramycin, and amikacin against recent isolates of P. aeruginosa and various Enterobacteriaceae.…”
mentioning
confidence: 99%
“…Chemically, it is 1-N-ethyl sisomicin, an analog of gentamicin Cla. Theoretical advantages of netilmicin are threefold: (i) an increased in vitro bactericidal activity over gentamicin against many strains of Enterobacteriaceae (1-3, 5, 6, 10, 11, 13, 15-17, 20, 22, 23); (ii) the inhibition of gentamicin-resistant strains when the resistance is associated with one of the gentamicininactivating acetylases (aminoglycoside acetylase-3i, -ii, or -iii) or an adenylase (aminoglycoside nucleotidylase-2"), which have been common modes of resistance among Enterobacter species, Escherichia coli, and Pseudomonas aeruginosa (4,16,18); (iii) relative freedom from ototoxicity and reduced nephrotoxicity in experimental animals (12,20). Also, there is a suggestion that the serum levels may be more predictable than those of gentamicin (19).…”
mentioning
confidence: 99%